Cortactin, a Lyn substrate, is a checkpoint molecule at the intersection of BCR and CXCR4 signalling pathway in chronic lymphocytic leukaemia cells. (17th April 2017) - Martini, Veronica; Gattazzo, Cristina; Frezzato, Federica; Trimarco, Valentina; Pizzi, Marco; Chiodin, Giorgia; Severin, Filippo; Scomazzon, Edoardo; Guzzardo, Vincenza; Saraggi, Deborah; Raggi, Flavia; Martinello, Leonardo; et al.
Summary: Cortactin (CTTN) is a substrate of the Src kinase Lyn that is known to play an actin cytoskeletal regulatory role involved in cell migration and cancer progression following its phosphorylation at Y421. We recently demonstrated that Cortactin is overexpressed in patients with chronic lymphocytic leukaemia (CLL). This work was aimed at defining the functional role of Cortactin in these patients. We found that Cortactin is variably expressed in CLL patients both in the peripheral blood and lymph nodes and that its expression correlates with the release of matrix metalloproteinase 9 (MMP‐9) and the motility of neoplastic cells. Cortactin knockdown, by siRNA, induced a reduction in MMP‐9 release as well as a decrease of migration capability of leukaemic B cells in vitro, also after chemotactic stimulus. Furthermore, Cortactin phosphorylation was lowered by the Src kinase‐inhibitor PP2 with a consequent decrease of MMP‐9 release in culture medium. An impaired migration, as compared to control experiments without Cortactin knockdown, was observed following CXCL12 triggering. Reduced Cortactin expression and phosphorylation were also detected both in vivo and in vitro after treatment with Ibrutinib, a Btk inhibitor. Our results highlight the role of Cortactin in CLL as a check‐point molecule between the BCR and CXCR4 signalling pathways.